Human animal relationships in Bos indicus cattle breeds addressed from a Five Domains welfare framework - Mota-Rojas, Daniel; Whittaker, Alexandra L.; Strappini, Ana C.; Orihuela, Agustín; Domínguez-Oliva, Adriana; Mora-Medina, Patricia; Álvarez-Macías, Adolfo; Hernández-Avalos, Ismael; Olmos-Hernández, Adriana; Reyes-Sotelo, Brenda; Grandin, Temple (Frontiers in Veterinary Science, 2024)
The present review has two objectives, the first is to investigate the differences in temperament between Bos indicus and Bos taurus breeds and determining the effects on production due to positive treatment and to compare this with negative HAR, by using the Five Domain Model as framework. The second objective is to discuss potential strategies to achieve better HAR when working with Bos indicus cattle. Bos indicus are more reactive and temperamental than Bos taurus cattle. When human animal relationships (HAR) are evaluated, Bos indicus cattle may react with greater intensity. They may be more likely to develop a negative emotional state, especially in extensively raised Bos indicus cattle that are handled only a few times each year. Bos indicus cattle can have positive emotional states when they have frequent positive interactions with people. Interactions with people, both positive and negative, would be in the fourth Domain of the Five Domains model. Cattle that are more reactive during handling may also have lower weight gain, even when they have abundant feed. This would be in the first Domain of Nutrition. When cattle are handled in races and corrals, injuries may be more likely to occur. Injuries and bruises would be in the third Domain of Health. Injuries could be caused by either poor handling practices by people or poor handling facilities. Yelling or electric prod use would be examples of poor HAR. Second Environmental Domain issues may be broken facilities or slick, slippery floors that are associated with falls.